Batik Ciprat Training for Students with Special Needs at Putra Pancasila SLB Foundation - Ahmad Hadi Wianto; Ajeng Leksana Mulia; Arina Salsabiela; Erfa Dinda Amalia; Firly Imaniar; Sartika Rahmawati; Ediyanto Ediyanto (PT FORMOSA CENDEKIA GLOBAL, 2023)
Batik is Indonesia's cultural heritage which is sustainable through inheritance from generation to generation. Batik is unique in terms of the motifs and techniques used. The aim of the splash batik training for students with special needs at Putra Pancasila SLB Foundation is to pass on a noble culture while at the same time equipping students with vocational skills that can support their lives. The splash technique was chosen based on the results of pre-implementation observations because it is simpler and can be followed by students with special needs at Putra Pancasila SLB Foundation. The methods used in this service are observation, demonstration, and training. The results of this training show that students with special needs are able to take part in the splash batik process from start to finish and the training participants are enthusiastic during the activity, especially during the process of splashing wax onto cloth using these 3 tools.